Some Generalized Forms of Fuzzy Interval Valued Hyperideals in a Hyperring - Hongjie Li; Zeyuan Li; Yunqiang Yin (Journal of Applied Mathematics)
Some generalized forms of the hyperideals of a hyperring in the paper of Zhan et al. (2008) will be given. As a generalization of the interval valued (α,β)-fuzzy hyperideals of a hyperring with α,β∈{∈,q,∈∧q,∈∨q} and α≠∈∧q, the notion of generalized interval valued (α,β)-fuzzy hyperideals of a hyperring is also introduced. Special attention is concentrated on the interval valued (∈γ~,∈γ~∨qδ~)-fuzzy hyperideals. As a consequence, some characterizations theorems of interval valued (∈γ~,∈γ~∨qδ~)-fuzzy hyperideals will be provided.